Strategi Pengembangan Agribisnis Berbasis Teknologi untuk Meningkatkan Produktivitas - Nisa Widia Agustira; Albert Jonatan Sigiro; Ersandi Roihan Putra; Viya Nur Sucianti Purba; Rizky Pariansyah Nasution (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The agribusiness sector plays a crucial role in the economy, especially in developing countries like Indonesia. However, traditional challenges such as limited land, climate change, and conventional farming practices often hamper productivity. Integration of technology in agribusiness offers innovative solutions to overcome these constraints and improve efficiency and yields. This study uses a descriptive qualitative approach with a literature study research design that focuses and aims to identify and analyze effective technology-based agribusiness development strategies to increase productivity sustainably. By exploring various technologies such as precision agriculture, Internet of Things (IoT), artificial intelligence (AI), and biotechnology, and their implementation in increasing productivity in various agribusiness subsectors. This study discusses the challenges and opportunities in technology adoption in the agribusiness sector, and recommends policies and strategies to encourage digital transformation in agriculture.